Water-based wind power blade finish paint and preparation method thereof

By optimizing the formula and process of water-based wind power blade topcoat, the problems of high cost and insufficient performance of wind power blade topcoat are solved, and low-cost and high-performance environmentally friendly coatings are realized, suitable for long-term protection of onshore and offshore wind power blades.

CN119119848APending Publication Date: 2024-12-13XIAMEN SUNRUI SHIP COATING
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411375976.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-30
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing wind power blade topcoat is costly and insufficient in performance, making it difficult to meet the needs of low-cost, high-performance environmentally friendly coatings. Especially in different environments of onshore and offshore wind farms, it faces multiple erosion challenges such as wind, sand and rain erosion.

Method used

A low-cost and high-performance aqueous wind power blade topcoat was developed, using a combination of component A and component B, including water, film forming additives, dispersants, defoaming agents, aqueous rheology additives, titanium dioxide , aqueous hydroxyacrylic emulsion, aqueous polyurethane dispersion, wax emulsion and other components, through the optimization of formula and process flow, the coating's medium resistance, weather resistance, wear resistance and rain corrosion resistance are improved.

Benefits of technology

It realizes the paint's drying rate, smooth construction, low VOCs, excellent mechanical properties and environmental adaptability, meets the long-term protection of onshore and offshore wind power blades, reduces the difficulty of production and construction, and at the same time, the domestic production rate is high and the cost advantage is obvious.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119119848A_ABST
    Figure CN119119848A_ABST
Patent Text Reader

Abstract

The invention relates to the technical field of paint, in particular to water-based wind turbine blade finish paint and a preparation method thereof. The water-based wind power blade finish paint comprises a component A and a component B, wherein the component A comprises water, a coalescing agent, a dispersing agent, a first defoaming agent, a water-based rheological agent, titanium dioxide, a wear-resistant filler, a water-based hydroxyl acrylic emulsion, a water-based polyurethane dispersion, a wax emulsion, a second defoaming agent and a base material wetting dispersing agent; and the component B comprises a water-based isocyanate curing agent and propylene glycol diacetate. The finish paint provided by the invention is high-performance environment-friendly water-based wind power blade finish paint, has the characteristics of high drying rate, smooth roller painting construction and the like, and is excellent in construction performance; meanwhile, the coating has low VOCs content, also has excellent mechanical properties, medium resistance, ultraviolet aging resistance, salt mist resistance, damp heat resistance, high and low temperature resistance, weather alternation resistance, wear resistance, rain erosion resistance, icing resistance, mold resistance and other protection properties, and can meet the long-acting protection requirements of wind turbine blades.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coating technology, and in particular to a water-based wind turbine blade topcoat and a preparation method thereof. Background Art

[0002] Wind turbines operate in harsh environments and are subject to long-term erosion from ultraviolet radiation, freezing, water vapor, wind and sand, rain erosion, etc. Wind turbine blades need to be protected by a coating system to extend maintenance cycles and increase investment returns.

[0003] At present, my country is accelerating the implementation of carbon emission reduction measures. Wind power generation has been rapidly developed as one of the main clean energy sources, and the wind turbine blade coating market has great development potential. However, the price of wind turbines has shown an accelerated downward trend, which will continue to compress the profit margin of wind turbine blade coatings. Therefore, how to develop a low-cost, high-performance and environmentally friendly wind turbine blade topcoat conforms to the development trend of cost reduction in the wind turbine coating market and has potential huge economic effects.

[0004] Wind turbine blade coating systems generally include putty, gel coat and topcoat. Topcoat is located on the surface of the wind turbine blade protective coating system, which not only determines the appearance of the wind turbine blade, but also directly contacts the external environment and resists erosion by light, heat, water, etc. This requires the topcoat to have excellent weather resistance and chemical resistance. At the same time, wind turbine blades are high-toughness materials, and they are under cyclic stress-strain for a long time during production, transportation and operation. Therefore, the protective coating system also needs to have high toughness to resist stress-strain fatigue.

[0005] In addition, according to the different sites, wind farms can be divided into onshore wind farms and offshore wind farms. The environments faced by wind turbine blades when operating in onshore and offshore wind farms are different. Onshore wind farms, especially in the northwest region, have strong winds and sandstorms, while offshore wind farms have strong winds, high waves, and more precipitation. Therefore, the coating protection system for onshore wind turbine blades and the coating protection system for offshore wind turbine blades have different focuses in performance. The onshore wind turbine coating system focuses on protection against wind and sand, while the offshore wind turbine coating system focuses on protection against rain erosion. At the same time, with the development of technology, the diameter of wind turbine blade impellers continues to increase. Generally, the diameter of offshore wind turbine impellers is larger than that of onshore blades. The trend of large-scale blades puts higher requirements on the toughness, rain erosion resistance, and wind and sand resistance of the protective coating system.

[0006] Existing wind turbine blade topcoats are divided into two types: solvent-based topcoats and water-based topcoats. Although some wind turbine blade manufacturers still use solvent-based topcoats, with the development of water-based technology, more environmentally friendly water-based topcoats have gradually replaced solvent-based topcoats. Environmentally friendly wind turbine blade coating systems have high technical indicators and are difficult to develop. The top three manufacturers in the wind turbine blade coating market are all large domestic coating companies or multinational companies with strong strength. However, the environmentally friendly wind turbine blade coating products of the above companies are expensive.

[0007] At present, the wind power industry is facing extremely severe cost pressure. Under cost pressure, installed wind turbines frequently break down. It is an urgent need for the wind power industry to develop a purely domestic low-cost, high-performance, environmentally friendly wind turbine blade coating system. In the wind turbine blade coating system, water-based wind turbine blade topcoat is the coating variety with the highest performance requirements except for the leading edge protection paint. How to break through the coating defect additive control technology to make the coating easy to produce and apply, and break through the key technologies such as material resistance to media, weather resistance, wear resistance and rain erosion resistance, develop a new domestic water-based wind turbine blade topcoat, and break the monopoly of high-priced products while ensuring that the coating meets the high performance requirements of wind turbine blade topcoat, is exactly the problem that technical personnel in this field are committed to solving. Summary of the invention

[0008] In order to solve the problems of the prior art mentioned in the above background technology, this application aims at the economic needs of cost reduction and efficiency improvement in the wind turbine blade industry, and provides a low-cost, high-performance, environmentally friendly water-based topcoat. The topcoat is easy to produce, transport, store and apply, has excellent low-temperature flexibility, medium resistance, weather resistance, wear resistance and rain erosion resistance, has excellent environmental adaptability, and is suitable for onshore and offshore wind turbine blades. The technical solution of this application is as follows:

[0009] The water-based wind turbine blade topcoat provided in the present application comprises component A and component B, wherein the component A comprises water, a film-forming aid, a dispersant, a first defoamer, a water-based rheological aid, titanium dioxide, a wear-resistant filler, a water-based hydroxy acrylic emulsion, a water-based polyurethane dispersion, a wax emulsion, a second defoamer, and a substrate wetting dispersant; the component B comprises a water-based isocyanate curing agent and propylene glycol diacetate; wherein the weight ratio of the film-forming aid, the first defoamer, the water-based rheological aid, the wear-resistant filler, the water-based hydroxy acrylic emulsion, the water-based polyurethane dispersion, the wax emulsion, and the second defoamer is (2-6): (0.1- 0.3): (0.05-0.3): (5.5-9.5): (36-43.2): (4.8-12): (2.5-4): (0.1-0.3); the solid content of the aqueous hydroxyl acrylic emulsion is (45-55)%, wherein the hydroxyl content is (1-2)% of the total mass of the aqueous hydroxyl acrylic emulsion resin; the solid content of the aqueous polyurethane dispersion is (40-50)%, wherein the hydroxyl content is (0-1.5)% of the total mass of the aqueous polyurethane dispersion resin; the wear-resistant filler is one or more combinations of feldspar powder, alum powder and quartz sand.

[0010] In some embodiments, the component A comprises, by weight: 9 to 13 parts of water, 2 to 6 parts of a film-forming aid, 0.3 to 0.6 parts of a dispersant, 0.1 to 0.3 parts of a first defoamer, 0.05 to 0.3 parts of an aqueous rheological aid, 18 to 27 parts of titanium dioxide, 5.5 to 9.5 parts of a wear-resistant filler, 36 to 43.2 parts of an aqueous hydroxylated acrylic emulsion, 4.8 to 12 parts of an aqueous polyurethane dispersion, 2.5 to 4 parts of a wax emulsion, and 0.1 to 0.3 parts of a second defoamer. .1 to 0.3 parts, 0.1 to 0.3 parts of base material wetting and dispersing agent and 0 to 0.8 parts of water-based color paste; the component B includes: 50 to 70 parts of water-based isocyanate curing agent and 30 to 50 parts of propylene glycol diacetate; the molar ratio of the isocyanate content of the water-based isocyanate curing agent in the component B to the hydroxyl value content of the resin in the component A is 1.3 to 2.5, wherein the resin in the component A is a water-based hydroxy acrylic emulsion and a water-based polyurethane dispersion.

[0011] In some embodiments, the first defoamer is one or more combinations of BYK-024, Tego810, and Tego901w; the second defoamer is one or more combinations of Tego902w, Tego823, Euka 290w, and Euka 295w.

[0012] In some embodiments, the aqueous hydroxylated acrylic emulsion is a secondary dispersion; the aqueous rheological additive is one or more combinations of WT-105A, U805, HDA519, COATEX XS71, RM2020, and BR125P.

[0013] In some embodiments, the wax emulsion is one or more combinations of PTFE-1004A and PTFE-1008.

[0014] In some embodiments, the substrate wetting and dispersing agent is one or more combinations of Tego wet 270, Tego Twin 4100, FX 600, and CF-10.

[0015] In some embodiments, the film-forming aid is one or more combinations of dipropylene glycol butyl ether and diethylene glycol monobutyl ether; the dispersant is one or more combinations of BYK-180, BYK-190, Euka 690w, SN5040, and X-405.

[0016] In some embodiments, the water is deionized water; the titanium dioxide is rutile titanium dioxide, which includes a mixture of one or more of R706, R996, and R5566; the water-based color paste is a mixture of one or more of water-based iron yellow paste Y2041-SI, water-based iron black paste SW809, and water-based royal blue paste B6420-SI.

[0017] In some embodiments, the water-based isocyanate curing agent is a polyether-modified water-based isocyanate curing agent or a sulfonate-modified water-based isocyanate curing agent, wherein the NCO- content is 18 to 23% of the total molecular weight of the curing agent, and its viscosity is 200 to 1000 cps; the propylene glycol diacetate is an urethane-grade solvent.

[0018] The present application also provides a method for preparing the water-based wind turbine blade topcoat as described above, which comprises the following steps:

[0019] According to the formula of component A, water, film-forming aid, dispersant, first defoamer and water-based rheological aid are mixed and dispersed evenly, and then titanium dioxide and wear-resistant filler are added and mixed, and ground to the fineness of the mixture is less than 30 microns; then, the paint is filtered out by a filter, and water-based hydroxy acrylic emulsion, water-based polyurethane dispersion, second defoamer and substrate wetting agent are added to the paint and mixed and dispersed evenly; finally, wax emulsion is added and continued to be mixed and dispersed evenly to obtain component A; according to the formula of component B, water-based isocyanate curing agent and propylene glycol diacetate are mixed and dispersed evenly to obtain component B.

[0020] Compared with the existing technology, the water-based wind turbine blade topcoat provided in this application has the following beneficial effects:

[0021] The topcoat provided in this application is a high-performance, environmentally friendly water-based wind turbine blade topcoat, which has the characteristics of fast drying rate, smooth roller coating construction, and excellent coating construction performance; the coating is an environmentally friendly coating with low VOCs (volatile organic compounds), and the coating also has excellent mechanical properties, medium resistance, UV aging resistance, salt spray resistance, humidity and heat resistance, high and low temperature resistance, climate alternation resistance, wear resistance, rain erosion resistance, anti-icing and mildew resistance and other coating protection properties, which can meet the long-term protection of onshore and offshore wind turbine blades. In short, the coating has excellent environmental adaptability and can be used as a topcoat for long-term protection of onshore and offshore wind turbine blades. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme in the embodiments of the present application will be clearly and completely described below in conjunction with the accompanying drawings. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of this application.

[0023] Figure 1 This is a surface state diagram of the samples of Comparative Examples 1-4 after alkali resistance test;

[0024] Figure 2 This is a surface state diagram of the samples of Comparative Examples 5-8 after alkali resistance test;

[0025] Figure 3 This is a surface state diagram of the samples of Comparative Examples 9-14 after alkali resistance test;

[0026] Figure 4 The surface state diagram of the samples of Example 1, Example 3 and Example 4 after alkali resistance test;

[0027] Figure 5 Surface state diagram of roller coating of Example 1 on solvent-free gel coat. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0029] The present application also provides the following embodiments and comparative examples:

[0030] The formulas of the examples and comparative examples of the present application are shown in Tables 1-5:

[0031] Table 1 Different resin ratio formula (unit, weight parts)

[0032]

[0033] Herein, the curing agent multiple refers to: the molar ratio of the isocyanate content of the water-based isocyanate curing agent in component B to the hydroxyl value content of the resin in component A; wherein the resin in component A refers to a water-based hydroxylated acrylic emulsion plus a water-based polyurethane dispersion.

[0034] In Table 1, the dispersant is Euka 690W; the first defoamer is Tego901w; the water-based rheological additive is U805; the titanium dioxide is rutile titanium dioxide, which is R996; the water-based hydroxy acrylic emulsion is a secondary dispersion with a solid content of 48%, wherein the hydroxyl content is 1.5% of the total mass of the water-based hydroxy acrylic emulsion resin; the water-based polyurethane dispersion is a secondary dispersion with a solid content of 49%, wherein the hydroxyl content is 1% of the total mass of the water-based polyurethane dispersion resin; the second defoamer is Tego810; the substrate wetting agent is Tego wet270; the NCO content of the polyether-modified water-based isocyanate curing agent is 18%, and the solid content is 100%.

[0035] Table 2 Alkali-resistant optimized formula (unit, parts by weight)

[0036]

[0037] In Table 2, the dispersant is Euka 690W; the first defoamer is Tego901w; the water-based rheological additive is U805; the titanium dioxide is rutile titanium dioxide, which is R996; the water-based hydroxy acrylic emulsion is a secondary dispersion with a solid content of 48%, wherein the hydroxyl content is 1.5% of the total mass of the water-based hydroxy acrylic emulsion resin; the water-based polyurethane dispersion is a secondary dispersion with a solid content of 49%, wherein the hydroxyl content is 1% of the total mass of the water-based polyurethane dispersion resin; the second defoamer is Tego810; the substrate wetting agent is Tego wet270; the NCO content of the sulfonate-modified water-based isocyanate curing agent is 20%, and the solid content is 100%.

[0038] Table 3 PVC optimized formula (unit, weight parts)

[0039]

[0040] In Table 3, the dispersant is Euka 690W; the first defoamer is Tego901w; the water-based rheological additive is U805; the titanium dioxide is rutile titanium dioxide, which is R996; the water-based hydroxy acrylic emulsion is a secondary dispersion with a solid content of 48%, wherein the hydroxyl content is 1.5% of the total mass of the water-based hydroxy acrylic emulsion resin; the water-based polyurethane dispersion is a secondary dispersion with a solid content of 49%, wherein the hydroxyl content is 1% of the total mass of the water-based polyurethane dispersion resin; the second defoamer is Tego810; the substrate wetting agent is Tego wet270; the NCO content of the sulfonate-modified water-based isocyanate curing agent is 20%, and the solid content is 100%.

[0041] Table 4 Wear-resistant optimized formula (unit, parts by weight)

[0042]

[0043]

[0044] In Table 4, the dispersant is Euka 690W; the first defoamer is Tego901w; the water-based rheological additive is U805; the titanium dioxide is rutile titanium dioxide, which is R996; the water-based hydroxy acrylic emulsion is a secondary dispersion with a solid content of 48%, wherein the hydroxyl content is 1.5% of the total mass of the water-based hydroxy acrylic emulsion resin; the water-based polyurethane dispersion is a secondary dispersion with a solid content of 49%, wherein the hydroxyl content is 1% of the total mass of the water-based polyurethane dispersion resin; the wax emulsion is PTFE-1004A; the second defoamer is Tego810; the substrate wetting agent is Tego wet270; the NCO content of the sulfonate-modified water-based isocyanate curing agent is 20%, and the solid content is 100%.

[0045] Table 5 Example 2 (unit, parts by weight)

[0046]

[0047]

[0048] In Table 5, the dispersant is Euka 690W; the first defoamer is Tego901w; the water-based rheological additive is U805; the titanium dioxide is rutile titanium dioxide, which is R996; the water-based hydroxy acrylic emulsion is a secondary dispersion with a solid content of 48%, wherein the hydroxyl content is 1.5% of the total mass of the water-based hydroxy acrylic emulsion resin; the water-based polyurethane dispersion is a secondary dispersion with a solid content of 49%, wherein the hydroxyl content is 1% of the total mass of the water-based polyurethane dispersion resin; the wax emulsion is PTFE-1004A; the second defoamer is Tego810; the substrate wetting agent is Tego wet270; the NCO content of the sulfonate-modified water-based isocyanate curing agent is 20%, and the solid content is 100%.

[0049] The preparation methods of the topcoat components A and B in Comparative Examples 1-14 and Examples 1-4 are as follows:

[0050] (1) Preparation process of component A:

[0051] Add deionized water, diethylene glycol butyl ether, dispersant, first defoamer, water-based color paste and water-based rheological additive into the iron can and disperse at 500r / min for 5min. Add titanium dioxide and feldspar powder, add enough zirconium beads, and sand grind at 1600r / min for 40min until the fineness is less than 30 microns. Then, filter out the paint with a 100-mesh filter, weigh the paint, put it in the iron can, deduct the loss, add water-based hydroxy acrylic emulsion, water-based polyurethane dispersion, second defoamer and substrate wetting agent in the formula ratio, disperse at high speed at 1000r / min for 5min, add wax emulsion (if there is no formula, it is not necessary to add), continue to disperse for 5min, and obtain component A.

[0052] (2) Preparation process of component B:

[0053] According to the formula ratio, the polyether modified water-based isocyanate curing agent or the sulfonate modified water-based isocyanate curing agent and propylene glycol diacetate are mixed, and dispersed at 500 r / min for 5 minutes to obtain component B.

[0054] Relevant tests were performed on the embodiments and comparative examples: the test methods were performed according to relevant test standards.

[0055] 1. Components A and B of Comparative Examples 1-4 were mixed according to the formula, stirred evenly, and subjected to tensile, wear resistance, alkali resistance and UV aging performance tests. The test results are shown in Table 6 and Figure 1 shown.

[0056] Table 6 Performance test results of comparative examples 1-4

[0057]

[0058]

[0059] Figure 1 The samples from left to right in the figure are comparative examples 1 to 4, wherein comparative examples 1 and 3 have no bubbling, and comparative examples 2 and 4 have bubbling.

[0060] It can be seen from Table 6 that when the polyurethane resin content increases from 10wt% to 25wt%, the coating strength first decreases from 10.03 to 8.43MPa, and then increases to 10.57MPa, and the elongation at break first increases from 87.69% to 136.63%, and then decreases to 122.5%. When the polyurethane resin content is 20wt%, the strength reaches the lowest value, and the elongation at break reaches the highest value. The strength and elongation of each formula meet the requirements. In addition, the higher the polyurethane content, the better the wear resistance. The wear resistance is between 112.8 and 130.4 mg, and the wear resistance does not meet the requirements; when the polyurethane resin content is 10wt% and 20wt%, there is no blistering in alkali resistance, and when the polyurethane resin content is 15wt% and 25wt%, there is blistering in alkali resistance, which indicates that the alkali resistance of the formula is unstable and still needs to be further improved; at the same time, the formulas in Table 7 are aged for 1500h under UVB-313, and slight powdering occurs, and the degree of powdering is level 1, and the UV aging performance of the formula needs to be further improved.

[0061] 2. Components A and B of Comparative Examples 5-8 were mixed according to the formula, stirred evenly, and subjected to tensile, wear resistance, alkali resistance and UV aging performance tests. The test results are shown in Tables 7 and Figure 2 shown.

[0062] Table 7 Performance test results of comparative examples 5-8

[0063]

[0064]

[0065] Figure 2 The samples from left to right in the figure are comparative examples 5 to 8, wherein comparative examples 5-8 have no blistering.

[0066] The alkali resistance of the coating is improved by using a sulfonate modified curing agent.

[0067] It can be seen from Table 7 that, compared with Comparative Examples 2 and 4, the sulfonate modified curing agent is used, and the alkali resistance of each formula is free of foaming, and the alkali resistance is improved; in addition, when the polyurethane resin content is 25wt%, when the curing agent multiple is increased from 1.4 to 1.8, the coating strength first increases from 8.76 to 9.33MPa, and then decreases to 7.36MPa, and the elongation at break first increases from 100.82% to 132.75%, and then decreases to 89.96%. When the curing agent multiple is 1.6, The strength and elongation at break are both optimal; in addition, the wear resistance of the comparative examples 5-7 is between 104.4 and 161.4, which do not meet the requirements and need to be further improved; when the polyurethane resin content is 25wt%, the curing agent multiples are 1.4 and 1.6, and the coatings are aged for 1500h under UVB-313, the degree of powdering is level 1, and when the curing agent multiple is 1.8, the coatings are aged for 1500h under the same conditions, and there is no powdering. Increasing the curing agent content improves the UV aging performance.

[0068] In addition, compared with Comparative Example 6, the polyurethane resin content of Comparative Example 8 is reduced to 15wt%, and although the strength and elongation at break are reduced to 8.61MPa and 91.09% respectively, they meet the requirements, the wear resistance is improved to 104.4mg, the UV aging resistance is improved, and the powdering is level 0. This shows that among the optimized alkali resistance formulas, Comparative Example 8 has the best performance, and its wear resistance still needs to be improved.

[0069] 3. Components A and B of Comparative Examples 9-14 were mixed according to the formula, stirred evenly, and subjected to tensile, wear resistance, alkali resistance and UV aging performance tests. The test results are shown in Table 8 and Figure 3 shown.

[0070] Table 8 Performance test results of comparative examples 9-14

[0071]

[0072]

[0073] Figure 3 The first column from top to bottom is Comparative Example 9 to Comparative Example 10, the second column from top to bottom is Comparative Example 11 to Comparative Example 12, and the third column from top to bottom is Comparative Example 13 to Comparative Example 14. Among them, Comparative Example 13 has a small amount of bubbles at the defects of the substrate, and the other samples have no bubbles.

[0074] On the basis of comparative example 8, the PVC (pigment volume concentration, the volume percentage of the powder in the dry film is called the pigment volume concentration) of the formula was further optimized, and the formulas of comparative examples 9-14 were designed.

[0075] It can be seen from Table 8 that when the curing agent multiple is 1.6 times and the feldspar powder content is increased from 5.5 to 9.5, the strength first decreases from 8.97MPa to 8.57MPa and then increases to 10.16MPa, and the elongation at break first decreases from 140.21% to 104.95% and then increases to 128.21%. Both the strength and elongation at break meet the requirements; the wear resistance increases from 125.8 to 97.2mg, there is no blistering in alkali resistance, and there is no powdering in UV aging resistance. When the feldspar powder content is 9.5, the performance is optimal. When the curing agent multiple is 2.0 times, the feldspar powder portion is increased from 5.5 to 9.5, the strength is increased from 6.74MPa to 11.47MPa, and the elongation at break is increased from 76.18% to 85.91% first, and then decreased to 69.7%. The strength and elongation at break meet the requirements; the wear resistance is increased from 125.8mg to 97.2mg, and the alkali resistance is no blistering except for the local substrate defect of comparative example 12, and there is no powdering in comparative example 10 and comparative example 14. The performance is optimal when the feldspar powder portion is 9.5. When the curing agent multiple is 1.6 and 2.0, the performance is better when the feldspar powder portion is 9.5, and the strength, wear resistance, alkali resistance and ultraviolet aging performance meet the requirements.

[0076] 4. Components A and B of Example 1 and Examples 3-4 were mixed according to the formula, stirred evenly, and subjected to tensile, wear resistance, alkali resistance and UV aging performance tests. The test results are shown in Tables 9 and Figure 4 shown.

[0077] Table 9 Performance test results of Example 1 and Examples 3-4

[0078]

[0079] Figure 4 The samples from left to right in the figure are Example 1, Example 3 and Example 4, wherein Example 1, Example 3 and Example 4 have no bubbles.

[0080] To further improve the wear resistance of the formulations of Comparative Example 13 and Comparative Example 14, wax emulsion was introduced into the formulations, and Example 1 and Examples 3-4 were designed.

[0081] It can be seen from Table 9 that when the wax emulsion is 3 to 4 parts, the coating strength is between 8.97 and 9.98 MPa, and the elongation at break is between 109.21 and 126.27%. The variation range of strength and elongation at break is small and meets the requirements. The wear resistance is between 40 and 57.4 mg, there is no blistering in alkali resistance, and there is no powdering in UV aging. Therefore, the introduction of 3 parts of wax emulsion has the best comprehensive performance. The introduction of 3 parts of wax emulsion to increase the wear resistance can significantly improve the wear resistance, and the strength, elongation at break, alkali resistance and UV aging of the formula have not decreased.

[0082] 5. Example 1 and Example 2 are the formulas of Comparative Example 13 and Comparative Example 14 after introducing 3 parts of wax emulsion. The comprehensive performance of the formulas of Example 1 and Example 2 was tested. The results are shown in Tables 10-12 and Figure 5 shown.

[0083] Table 10 Comprehensive performance test results of Example 1 and Example 2

[0084]

[0085] Table 11 Comprehensive performance test results of Example 1 and Example 2

[0086]

[0087]

[0088] Table 12 Comprehensive performance test results of Example 1 and Example 2

[0089]

[0090] Note: Although both Table 9 and Tables 10-12 have performed performance tests on Example 1, since the samples tested in the two sets of data are from different batches, there are differences in some data between the two tests of Example 1. It is normal for the performance data of different batches of products to differ and fluctuate.

[0091] Figure 5 It can be seen that the surface of the roller coating of Example 1 on the solvent-free gel coat (the gel coat is 725-S06-15 solvent-free polyurethane gel coat) is smooth without bubbles and pinholes. Similarly, the surface of the roller coating of Example 2 on the gel coat is also smooth without bubbles and pinholes (no figure, text description).

[0092] From Table 10-12, we can see that

[0093] Example 1 and Example 2 have excellent construction performance, the coating has a fast drying rate, the surface is dry for 15 minutes, and after roller coating, the paint film has a smooth surface without bubbles and pinholes; the coating has good environmental adaptability, freeze-thaw resistance passes, and storage stability is 12 months. The coating is an environmentally friendly coating with VOCs at 51.3-52.4 g / L. The coating performance of Example 1 and Example 2 is excellent, with adhesion of 15.27 and 14.88 MPa respectively; elongation at break of 91.32% and 76.38% respectively; flexibility (-40°C) of 1 mm; impact resistance (-40°C) ≥50 cm; abrasion resistance of 68 and 56.9 mg respectively; gloss (60°) of 11.4 and 10.2 respectively; water contact angles of 104.15° and 100.3° respectively; salt spray resistance of 3000h, passed; resistance to artificial accelerated aging (UVB-313) of 1500h, passed; climate alternation test of 1000h, passed; moisture and heat resistance of 1000h, passed; water resistance, oil resistance, acid resistance and alkali resistance of 240h, no blistering and shedding; rain erosion resistance of 2h, passed; mildew resistance level 1.

[0094] Therefore, the water-based wind turbine blade topcoat developed in the embodiment of the present application is a high-performance environmentally friendly coating with excellent environmental adaptability. It can be used as a topcoat for the protection of onshore and offshore wind turbine blades. Through the above-mentioned technical route, the relevant technical problems and defects existing in the prior art can be solved.

[0095] In summary, the present application scheme has at least the following design concepts and beneficial effects:

[0096] 1. Design concept:

[0097] (1) Drying rate control technology:

[0098] The hydroxy acrylic acid and waterborne polyurethane used in this application are both self-drying resins. By increasing the content of the self-drying resin and reducing the amount of curing agent, the surface drying process of the coating is changed from being driven mainly by a chemical process to being driven mainly by a physical drying process, so that the coating surface is dried after the water evaporates, greatly improving the drying rate of the coating. In addition, the PVC is adjusted so that the coating surface is dry enough after the water evaporates, shortening the waiting time for the second topcoat.

[0099] (2) Paint film mechanical properties control technology:

[0100] This application optimizes the design of the film-forming system and filler composition, and uses a highly flexible waterborne polyurethane modified hydroxy acrylic resin to improve the flexibility of the film-forming material. By optimizing the proportion of waterborne polyurethane in the resin, a film-forming material with excellent mechanical strength and flexibility is obtained; in addition, by studying the filler composition, it is found that the paint film with a specific proportion of fillers has better mechanical properties, and the type and composition of the filler have a significant effect on the mechanical properties of the coating. Therefore, this application achieves the regulation of the mechanical properties of the paint film by optimizing the design of the film-forming system and filler composition, and obtains a highly flexible, high-strength and highly wear-resistant waterborne topcoat.

[0101] (3) High alkali resistance:

[0102] The carbamate groups in the waterborne polyurethane structure can be hydrolyzed under alkaline conditions, causing the coating to fail. Therefore, improving the alkali resistance of waterborne polyurethane is a major difficulty. In order to make the polyurethane coating highly alkali-resistant, the present application uses a resin with a low hydroxyl content. The resin has a large molecular weight and forms fewer carbamate structures through cross-linking reactions with isocyanates, which reduces the sites where the film-forming material is easily hydrolyzed. Moreover, after partial hydrolysis of the carbamate, the coating still has good adhesion strength due to the high cross-linking density of the resin itself.

[0103] (4) High weather resistance:

[0104] The topcoat of wind turbine blades is matte coating. However, the introduction of matting powder in matte coating usually leads to a significant decrease in the weather resistance of the coating. This application adopts a low-gloss resin-curing agent system and optimizes the PVC formula to achieve a matte effect of the paint film without using matting powder, which greatly improves the weather resistance of the matte topcoat.

[0105] (5) Paint roller coating technology:

[0106] During the roller coating process, since the roller hair is not uniform and continuous, after the roller hair absorbs the paint, the pressure of squeezing the paint at the coating site is also uneven, which inevitably leads to roller marks. Therefore, the coating that is easy to roll needs to have excellent leveling properties; in addition, the rolling of the roller generates a huge shear force at the coating site, which easily introduces external air and causes a large number of bubbles to appear in the wet film. Therefore, the coating that is easy to roll needs to have excellent defoaming properties. In particular, the coating matrix in the present application is a quick-drying coating with a fast surface drying speed and a short defoaming time. This performance is not conducive to roller coating construction. Therefore, in order to solve the problem of poor surface state of roller coating construction, the present application adopts an unstable low-shear rheological additive to strictly control the roller coating viscosity of the coating and reduce the bubbles generated by roller coating. At the same time, the low-shear rheological additive makes the coating have an excellent static thixotropic effect, small dynamic roller coating resistance, and is also helpful to introduce more diluents. The paint film has a high flatness after drying; by adopting and optimizing a strong defoamer system, the defoaming ability of the coating is improved, making the coating easy to defoam and break bubbles; by adopting an unstable substrate wetting agent, the wettability of the coating to the substrate is improved, and the surface flatness of the paint film is improved. Therefore, in the present application, through the synergistic effect of additives in three aspects, such as thixotropy, defoaming, and substrate wetting, the problems of bubbles, shrinkage holes, and poor surface flatness that are easily generated during roller coating construction are solved, making the coating easy to roller coating construction.

[0107] 2. Beneficial effects:

[0108] This application adopts a low-gloss hydroxy acrylic-polyisocyanate resin-curing agent system, introduces a flexible polyurethane resin for toughening, and prepares a two-component water-based acrylic polyurethane topcoat. This application controls the source of materials, and the localization rate of raw materials reaches more than 99%, reducing product costs; breaking through the coating defect auxiliary agent control technology, making the coating easy to produce and apply; breaking through the key technologies of material resistance to media, weather resistance, wear resistance and rain erosion resistance, and obtaining a high-performance environmentally friendly water-based topcoat suitable for onshore and offshore wind turbine blades.

[0109] The topcoat provided in this application is a high-performance, environmentally friendly water-based wind turbine blade topcoat, which has the characteristics of fast drying rate, smooth roller coating construction, and excellent coating construction performance; the coating is an environmentally friendly coating with low VOCs (volatile organic compounds), and the coating also has excellent mechanical properties, medium resistance, UV aging resistance, salt spray resistance, humidity and heat resistance, high and low temperature resistance, climate alternation resistance, wear resistance, rain erosion resistance, anti-icing and mildew resistance and other coating protection properties, which can meet the long-term protection of onshore and offshore wind turbine blades. In short, the coating has excellent environmental adaptability and can be used as a topcoat for long-term protection of onshore and offshore wind turbine blades.

[0110] In summary, the high-performance environmentally friendly water-based wind turbine blade topcoat provided by this application is easy to produce, transport, store and construct, has excellent low-temperature flexibility, medium resistance, weather resistance, wear resistance and rain erosion resistance, has excellent environmental adaptability, and is suitable for onshore and offshore wind turbine blades. At the same time, the localization rate of raw materials exceeds 99%, and the product has cost advantages.

[0111] It should be noted that:

[0112] In this article, “~” is used to indicate a numerical range, and the range indicated by this expression includes two endpoint values.

[0113] In addition to the actual selections embodied in the above specific embodiments, the above formulation ranges may be used in the specific implementation of the present application, including but not limited to the above embodiment schemes.

[0114] The specific parameters or some commonly used reagents or raw materials in the above embodiments are specific embodiments or preferred embodiments of the present application, but are not intended to limit the present application. Those skilled in the art may make adaptive adjustments within the scope of the present application.

[0115] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit it. Although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present application.

Claims

1. A water-based wind turbine blade topcoat, comprising component A and component B, characterized in that: The component A includes water, film-forming aid, dispersant, first defoamer, water-based rheological aid, titanium dioxide, wear-resistant filler, water-based hydroxy acrylic emulsion, water-based polyurethane dispersion, wax emulsion, second defoamer, substrate wetting dispersant; the component B includes water-based isocyanate curing agent and propylene glycol diacetate; The weight ratio of the film-forming aid, the first defoamer, the aqueous rheological aid, the wear-resistant filler, the aqueous hydroxy acrylic emulsion, the aqueous polyurethane dispersion, the wax emulsion, and the second defoamer is (2-6): (0.1-0.3): (0.05-0.3): (5.5-9.5): (36-43.2): (4.8-12): (2.5-4): (0.1-0.3); The solid content of the aqueous hydroxyl acrylic emulsion is (45-55)%, wherein the hydroxyl content is (1-2)% of the total mass of the aqueous hydroxyl acrylic emulsion resin; the solid content of the aqueous polyurethane dispersion is (40-50)%, wherein the hydroxyl content is (0-1.5)% of the total mass of the aqueous polyurethane dispersion resin; The wear-resistant filler is one or more combinations of feldspar powder, alum powder and quartz sand.

2. The water-based wind turbine blade topcoat according to claim 1, characterized in that: Measured by weight, the component A comprises: 9 to 13 parts of water, 2 to 6 parts of film-forming aid, 0.3 to 0.6 parts of dispersant, 0.1 to 0.3 parts of first defoamer, 0.05 to 0.3 parts of water-based rheological additive, 18 to 27 parts of titanium dioxide, 5.5 to 9.5 parts of wear-resistant filler, 36 to 43.2 parts of water-based hydroxy acrylic emulsion, 4.8 to 12 parts of water-based polyurethane dispersion, 2.5 to 4 parts of wax emulsion, 0.1 to 0.3 parts of second defoamer, 0.1 to 0.3 parts of substrate wetting dispersant and 0 to 0.8 parts of water-based color paste; The component B comprises: 50-70 parts of water-based isocyanate curing agent and 30-50 parts of propylene glycol diacetate; The molar ratio of the isocyanate content of the water-based isocyanate curing agent in the component B to the hydroxyl value content of the resin in the component A is 1.3-2.5, wherein the resin in the component A is a water-based hydroxy acrylic emulsion and a water-based polyurethane dispersion.

3. The water-based wind turbine blade topcoat according to claim 1, characterized in that: The first defoamer is one or more of BYK-024, Tego810, and Tego901w; The second defoaming agent is one or more combinations of Tego902w, Tego823, Euka 290w, and Euka 295w.

4. The water-based wind turbine blade topcoat according to claim 1, characterized in that: The aqueous hydroxylated acrylic emulsion is a secondary dispersion; The aqueous rheological additive is one or more combinations of WT-105A, U805, HDA519, COATEX XS71, RM2020, and BR125P.

5. The water-based wind turbine blade topcoat according to claim 1, characterized in that: The wax emulsion is one or more combinations of PTFE-1004A and PTFE-1008.

6. The water-based wind turbine blade topcoat according to claim 1, characterized in that: The substrate wetting and dispersing agent is one or more combinations of Tegowet270, Tego Twin4100, FX 600 and CF-10.

7. The water-based wind turbine blade topcoat according to claim 1, characterized in that: The film-forming aid is one or more combinations of dipropylene glycol butyl ether and diethylene glycol monobutyl ether; The dispersant is one or more combinations of BYK-180, BYK-190, Euka 690w, SN5040, and X-405.

8. The water-based wind turbine blade topcoat according to claim 2, characterized in that: The water is deionized water; The titanium dioxide is rutile titanium dioxide, which includes a mixture of one or more of R706, R996, and R5566; The water-based color paste is a mixture of one or more of water-based iron yellow paste Y2041-SI, water-based iron black paste SW809, and water-based royal blue paste B6420-SI.

9. The water-based wind turbine blade topcoat according to claim 1, characterized in that: The water-based isocyanate curing agent is a polyether-modified water-based isocyanate curing agent or a sulfonate-modified water-based isocyanate curing agent, wherein the NCO- content is 18-23% of the total molecular weight of the curing agent, and the viscosity is 200-1000 cps; The propylene glycol diacetate is a urethane grade solvent.

10. A method for preparing a water-based wind turbine blade topcoat according to any one of claims 1 to 9, characterized in that: The following steps are involved: According to the formula of component A, water, film-forming aid, dispersant, first defoamer and water-based rheological aid are mixed and dispersed uniformly, and then titanium dioxide and wear-resistant filler are added and mixed, and ground until the fineness of the mixed material is less than 30 microns; then, the paint is filtered out by a filter screen, and water-based hydroxy acrylic emulsion, water-based polyurethane dispersion, second defoamer and substrate wetting agent are added to the paint and mixed and dispersed uniformly; finally, wax emulsion is added and continued to be mixed and dispersed uniformly to obtain component A; According to the formula of component B, the water-based isocyanate curing agent and propylene glycol diacetate are mixed and dispersed uniformly to obtain component B.

Citation Information

Patent Citations

  • Water-based coating and preparation method and application thereof

    CN102533078A

  • Water-borne bi-component white gloss topcoat and preparation method thereof

    CN105505169A

  • Quick-drying roller coating type water-based wind turbine blade finish paint and preparation method thereof

    CN116676032A

  • Water-based wind turbine blade finish paint with excellent alkali resistance and weather resistance and preparation method thereof

    CN118291025A